The Automated Information System “Perimeter” is a Tool for the Modernization of Information and Technical Support of Sanitary and Quarantine Control - A. Yu. Popova; E. B. Ezhlova; V. Yu. Smolensky; A. N. Letyushev; A. A. Treskin; A. V. Ivanova; V. A. Safronov; A. A. Zubova; I. G. Karnaukhov; V. P. Toporkov; S. A. Shcherbakova; V. V. Kutyrev (Проблемы особо опасных инфекций)
Sanitary and quarantine control (SQC) at the state border of the Russian Federation is the first barrier to the importation and subsequent spread of diseases on the territory of the country. Every year the number of registered outbreaks of infectious diseases in the countries of the world increases, which entails an increase in published information, some of which is unreliable and requires verification. At the same time, against the background of the development of international tourism, increase in passenger traffic, the risk of infectious diseases importation into the territory of Russia rises manifold, which creates the need for modernization of information and technical support of the SQC. In connection with the above, the aim of the work was to develop a scientifically substantiated system of informatization and digitalization of SQC, which resulted in the introduction of an automated risk assessment system as regards importation of dangerous infectious diseases (AIS “Perimeter”) at all sanitary-quarantine checkpoints (SQP). Materials and methods. The information system was created using the following software platforms: Laravel, VueJs. The official websites of the Ministries of Health of the respective countries, data from the official regional websites of WHO, regional centers for disease control and prevention (CDC), and data from the ProMED-mail system were used as sources of information on infectious morbidity in the countries of the world. Results and discussion. Implementation of AIS “Perimeter” has brought about the maximum possible efficiency in the targeted informing of SQP officials about the current epidemiological situation in the countries of the world; an effective tool for monitoring the situation at the federal level in real-time mode. It facilitates the work of SQP, staff related to conducting standard operational procedures, due to considerable decrease in the volume of routine activities to keep records. The proposed in the AIS expert risk assessment as regards importation of infectious diseases allows SQP employees, based on reliable information, to make timely decisions on the need to conduct SQC and exclude erroneous actions in the essential set of measures within the framework of SQC implementation, while minimizing subjectivity with respect to decision making.